A need of time: Android Security - Prashant.V, Mr.; Devadiga, Mr. Nagendra; C.P, Mrs.Vandana. (IJRDO -Journal of Computer Science Engineering, 2016)
With millions of free applications on theAndroid Store, users are tempted to download theseapplications. These apps maybe games or anyproductive app like Antivirus or Office related apps.Smartphones have become a big essential toeveryone’s life. Since user confidential data isaccessed by these applications, the user security is atthreat. In this paper, the various aspects of securityattack in android is analyzed, particularly attacks usingcameras.